Рeculiarities of professional training organization of masters sіls llm degree program in “international commercial law and dispute resolution” - Нагорна, Ольга Олександрівна (ScienceRise: Pedagogical Education, 2016)
The SiLSLL.M. in International Commercial Law and Dispute Resolution is taught fully online, giving career professionals access to a level of higher education. Its purpose is to facilitate worldwide teaching and learning of international commercial law and alternative dispute resolution. The global curriculum of the program is not linked to one specific jurisdiction, but strongly based on a genuine comparative approach. All scholars and experts teaching at SiLS have a strong background in the international academic world as well as in practice. The SiLS LL.M. master degree is awarded upon the satisfactory completion of four interactive modules and four self-guided tutorials.Each module engages students in supervised group projects and online activities in groups of mixed cultural and legal background, which complements individual study